The Propensity of SMEs to Innovate: A Cross – Country Outlook - Fafaliou, Irene; Stefanitsis, Marinos; Skaržauskienė, Aelita (SPOUDAI Journal of Economics and Business, 2014)
Although small and medium-sized enterprises’ (SMEs) involvement in the innovation process is a long standing issue and recently has resurged in the relevant literature, building and sustaining innovation is a hard and non linear work. The purpose of the paper is to explore the propensity of SMEs to innovate drawing evidence from three different countries and a wide variety of sectors and firms’ ages and sizes. In particular, this paper focuses on differences between various characteristics of the surveyed SMEs and attempts to establish links with firms’ tendency to innovate. Data were collected through a questionnaire survey addressed to a sample of 336 firms located in Greece, Croatia, and Lithuania. Findings suggest a somewhat problematic relationship between Greek and Croatian firms and their involvement to innovation. Lithuanian firms, however, seem to be more committed to innovation since they employ a more dynamic approach to innovation process and its implementation. JEL Classification: O31; L20; O57.